Contextualising the Right to Life and the Phenomenon of Mob Justice in South Africa / Marrien Sibanda - Sibanda, Marrien (2015)
This mini-dissertation seeks to investigate the harm caused by mob justice to people who are endowed with the right to life that is entrenched in the Bill of Rights. The investigation is done against the backdrop of an elaborate Bill of Rights that makes the right to life inviolable in democratic South Africa. It exposes the factors that underlie the growing incidence of mob justice in the country and the implications of this phenomenon for legal and policy options. The mini-dissertation proceeds from the understanding that the state has a duty to protect the right to life and that mob justice is unconstitutional and violates the right to life and its associated rights like the section 35 rights, right to dignity and so on. It is necessary that the state acts upon this phenomenon so as to fulfil its constitutional duty to protect the right to life. Beyond the analysis of the incidence of mob justice in South Africa, an effort was made to proffer viable strategic responses to curb the phenomenon in the short and long terms. === Thesis (LLM) North-West University, Mafikeng Campus, 2014